Issues to be solved within the framework of semantic research in forensic linguistic expertise - Otajonova , Dildor (The Lingua Spectrum, 2025)
This article examines the role and main tasks of semantic research within forensic linguistic expertise. The interaction of legal and linguistic approaches, the subject of semantic expertise, and methodological tools are analyzed. The legal significance of expertise results is also discussed.